X-ray spectroscopic observation of an interstitial carbide in NifEN-bound FeMoco precursor - Lancaster, Kyle M; Hu, Yilin; Bergmann, Uwe; Ribbe, Markus W; DeBeer, Serena (Journal of the American Chemical Society, 2013)
The iron-molybdenum cofactor (FeMoco) of nitrogenase contains a biologically unprecedented μ(6)-coordinated C(4-) ion. Although the role of this interstitial atom in nitrogenase catalysis is unknown, progress in understanding its biosynthetic origins has been made. Here we report valence-to-core Fe Kβ X-ray emission spectroscopy data to show that this C(4-) ion is present in the Fe(8)S(9) "L-cluster," which is the immediate precursor to FeMoco prior to the insertion of molybdenum and coordination by homocitrate. These results accord with recent evidence supporting a role for the S-adenosylmethionine-dependent enzyme NifB in the incorporation of carbon into the FeMoco center of nitrogenase.